The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12889-019-6399-8
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities for eliminating tuberculosis – leveraging political momentum of the UN high-level meeting on tuberculosis

Abstract: BackgroundAs demonstrated by the United Nations High-Level Meeting on tuberculosis (TB) held in September 2018, the political momentum for TB has been increasing. The aim of this study was to analyze the current challenges and opportunities for global TB control and, with specific focus on policies surrounding TB control, to reveal what kinds of efforts are needed to accelerate global TB control.MethodsWe organized two expert meetings with the purposes of assessing the current situation and analyzing challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 16 publications
0
28
0
5
Order By: Relevance
“…Annually, about 1.6 million die from tuberculosis (TB) [1], with 9.4 million new cases around the world [2]. TB is the leading cause of death globally, surpassing HIV since 2014 [3,4]. Because TB is highly infectious, each person with undiagnosed and untreated smear-positive TB is estimated to cause 10-14 infections per year, where about 10% would eventually become a new case of TB [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Annually, about 1.6 million die from tuberculosis (TB) [1], with 9.4 million new cases around the world [2]. TB is the leading cause of death globally, surpassing HIV since 2014 [3,4]. Because TB is highly infectious, each person with undiagnosed and untreated smear-positive TB is estimated to cause 10-14 infections per year, where about 10% would eventually become a new case of TB [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, multidrug-resistant and extensively drug-resistant TB (MDR/XDR-TB) have become global public health threats. There are many TB patients who have no access to health care facilities or proper diagnosis and treatment [4]. In 2018, Heads of State at the United Nations called for action to end TB 3 .…”
Section: Introductionmentioning
confidence: 99%
“…An essential aspect of TB is the substantial financial burden placed on patients and their families due to treatment and associated costs. For example, TB patients are often required to take absence leave from work, which, is unpaid in some cases, leading to a higher risk of financial struggle in the household [51]. Tanimura et al reported the distribution of financial burden for the TB patient as 20% due to direct medical costs, 20% due to direct non-medical costs, and 60% due to income loss [52].…”
Section: Early Assessment Of Tuberculosis In Vulnerable Populationsmentioning
confidence: 99%
“…Tuberculosis (TB) caused by Mycobacterium tuberculosis is among the top 10 causes of death worldwide [1], and represents serious challenges that faces the global disease eradication policy owing to the growing antimicrobial resistance [2,3]. TB kills annually around 1.5 million people with over 80% in the developing countries including India, China, Indonesia, Philippines, Pakistan, Nigeria, Bangladesh and South Africa [4].…”
Section: Introductionmentioning
confidence: 99%